High chloride channel accessory 1 expression predicts poor prognoses in patients with rectal cancer receiving chemoradiotherapy - Chen, Tzu-Ju (Int J Med Sci, 2018)
Background: Concurrent chemoradiotherapy (CCRT) has now become the standard of treatments for advanced rectal cancer before surgery. To search the biological molecules with prognostic and therapeutic potential of CCRT could be beneficial for these patients. Recently, aberrant expression of chloride channels has been linked to radio-resistance in glioblastoma; however, its clinical implication has not been well-studied in rectal cancers. Therefore, we examined the clinical significance of targetable drivers associated with chloride channel activity in patients with rectal cancer receiving CCRT. Methods: After datamining from a published transcriptome of rectal cancers, upregulation of CLCA1 gene was recognized to be significantly correlated with non-responders of CCRT. In validation cohort of rectal cancers, the expression levels of CLCA1 were accessed by using immunohistochemistry assays in 172 tumor specimens that were obtained before any treatment. Expression levels of CLCA1 were statistically analyzed with principal clinicopathological features and survival outcomes in this substantial cohort. Results: In validation cohort, high expression of CLCA1 was significantly associated with higher pre-treatment tumor nodal stages (P=0.032), vascular invasion (P=0.028), and inferior tumor regression grade (P=0.042). In survival evaluations, high expression of CLCA1 was significantly correlated with worse local recurrence-free survival (LRFS; P=0.0012), metastasis-free survival (MeFS; P =0.0114), and disease-specific survival (DSS; P=0.0041). Furthermore, high expression of CLCA1 remained an independent prognosticator of shorter LRFS (P=0.029, hazard ratio=2.555), MeFS (P=0.044, hazard ratio=2.125) and DSS (P=0.044, hazard ratio=2.172). Conclusions: High expression of CLCA1 is significantly associated with poor therapeutic response and survival outcomes in rectal cancer patients with CCRT treatment before surgery. With the development of specific inhibitors, our findings indicate not only prognostic but also therapeutic potential of CLCA1 in rectal cancers.